2019
DOI: 10.1186/s13046-019-1388-4
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA 00976 promotes pancreatic cancer progression through OTUD7B by sponging miR-137 involving EGFR/MAPK pathway

Abstract: Background: Accumulation evidence indicates the vital role of long non-coding RNAs (lncRNAs) in tumorigenesis and the progression of malignant tumors, including pancreatic cancer (PC). However, the role and the molecular mechanism of long non-coding RNA 00976 is unclear in pancreatic cancer. Methods: In situ hybridization (ISH) and qRT-PCR was performed to investigate the association between linc00976 expression and the clinicopathological characteristics and prognosis of patients with PC. Subsequently, linc00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…As previously reported, lncRNAs could complete with the binding of miRNA to promote the target gene expression in transcription and translation [ 22 24 ]. Also, lncRNA/miRNA and the target gene-mediated ceRNA regulation network has been shown in PC progress [ 16 , 18 ]. Our functional assay demonstrated that PSMB8-AS1 could act as the upstream gene of miRNA-382–3p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, lncRNAs could complete with the binding of miRNA to promote the target gene expression in transcription and translation [ 22 24 ]. Also, lncRNA/miRNA and the target gene-mediated ceRNA regulation network has been shown in PC progress [ 16 , 18 ]. Our functional assay demonstrated that PSMB8-AS1 could act as the upstream gene of miRNA-382–3p.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the competing endogenous RNA (ceRNA) regulation network is the most frequently reported molecular mechanism to elucidate the function in tumor biology progress [16][17][18][19]. Therefore, miRNA as the pivotal downstream of lncRNA mediated tumorigenesis via regulation of the target gene.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli such as oxidative stress can make phosphatidylserine appear outside on the pancreatic cancer cell membrane, finally leading to dysregulation of factors and cells such as VEGF and macrophages, making prognosis of patients unfavorable [ 66 68 ]. The EGFR pathway contributes to pancreatic cancer growth and accelerates invasion of the cancer as a result of lnc00976 overexpression, which can deteriorate the outcome of patients [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulations such as oxidative stress can make phosphatidylserine appear outside on the pancreatic cancer cell membrane, nally leading to dysregulation of factors and cells like VEGF and macrophages, making prognosis of patients unfavorable (66)(67)(68). The EGFR pathway contributes to pancreatic cancer growth and accelerates invasion of the cancer as a result of linc00976 overexpression, which can deteriorate outcome of patients (69,70).…”
Section: Discussionmentioning
confidence: 99%